Evaluation of canthinone alkaloids as cerebral protective agents - Sasaki, Tatsunori; Li, Wei; Ohmoto, Taichi; Koike, Kazuo (Bioorganic & Medicinal Chemistry Letters, 2016)
[Display omitted] •Five canthinone alkaloids were shown to be cerebral protective agents.•N-3, C-4, and C-9 substitutions affect the cerebral protective effect.•Picrasidine O suppresses neuronal hyperexcitability caused by glutamic acid.•Picrasidine O shows improvement effects on brain tissue damage.•Picrasidine O has no effect on heart rate or mean systolic blood pressure. Considerable attention has been paid to cerebral protective drugs as a potential therapy for dementia. Screening of a natural compound library here resulted in identification of five canthinone alkaloids, viz., picrasidine L (1), picrasidine O (2), eurycomine E (3), 3-ethyl-canthin-5,6-dione (4), and 3-ethyl-4-methoxy-canthin-5,6-dione (5), as novel cerebral protective agents. The structure–activity relationship indicated that C-4, C-9, and N-3 substitutions greatly affected their cerebral protective effect. Among these, compound 2 exhibited a cerebral protective effect through suppressing neuronal hyperexcitability due to an increase in the excitatory neurotransmitter glutamic acid. Furthermore, compound 2 did not affect heart rate and mean systolic blood pressure. This investigation suggests that compound 2 has potential for further development as a cerebral protective drug.